L’esquisse du genre - Simon Massei (Genre, Sexualité et Société)
In a genealogical and diachronic approach, this article aims to describe the representations of masculinity and femininity in Disney’s full length animated movies since 1937, and the evolution of these representations over the last decades. Methodologically, it is based on the viewing and the qualitative analysis of fifteen movies, every one tracing the romance of a heterosexual couple. Using primary and secondary sources, this article proposes in the first instance a short literary and political genealogy of the femininities and masculinities depicted in Disney’s full length animated movies. The analysis then moves on to the symbolic distribution of spaces and skills between male and female characters, the nature/culture opposition and the inside/outside division. At last, this article examines, from the perspective of gender the links between body, morality, masculinity and femininity among positive and negative characters.